Extreme population subdivision or cryptic speciation in the cactus Pilosocereus jauruensis? A taxonomic challenge posed by a naturally fragmented system. Issue 2 (17th February 2018) - Khan, Gulzar; Godoy, Mariana O.; Franco, Fernando F.; Perez, Manolo F.; Taylor, Nigel P.; Zappi, Daniela C.; Machado, Marlon C.; Moraes, Evandro M.
Abstract : In allopatric systems, where gene flow is highly constrained, the distinction between intraspecific differentiation and speciation is a challenging task. Pilosocereus jauruensis is a columnar cactus restricted to patchy dry habitats of Pantanal, Cerrado, and Chaco biomes in south-western Brazil and neighbouring countries. This species was recently reinstated after having been synonymized with P. machriisi, now including P. paraguayensis, P. saudadensis, and P. densivillosus as its synonyms. These taxa have been placed within the informal Aurisetus group. The present study aimed to investigate the genetic structure of P. jauruensis in order to identify possible distinct evolutionary lineages, and to support further refinement of the taxonomy of this species. For this purpose, 10 microsatellite loci were genotyped for 156 individuals of P. jauruensis . To provide a proxy for the expected interspecific differentiation level within this allopatric system, two populations (49 individuals) of P. vilaboensis (a species closely related to P. jauruensis ) were also included. Additionally, two cpDNA markers ( trnSGCU-trnGUCC and trnT-trnL ) for a subsample of 44 individuals of both species were sequenced. The results obtained showed that even though P. jauruensis populations are relatively small and isolated, they still maintain a high level of genetic diversity (e.g., HE = 0.557 to 0.725; HO = 0.253 to 0.409). The study suggests the existence of two distinct taxa/evolutionary lineages through their entire distribution. Two populations found in the same geographic region of the now synonymized P. densivillosus showed significant genetic divergence when compared with other populations of P. jauruensis . In contrast, our results did not support an evolutionary independence hypothesis for populations that occur in the same geographic region of the synonymous P. saudadensis .